Transcription of Subgenomic mRNA of Hepatitis Delta Virus Requires a Modified Hepatitis Delta Antigen That Is Distinct from Antigenomic RNA Synthesis - Tseng, Chung-Hsin (American Society for Microbiology (ASM), 2008)
Hepatitis delta virus (HDV) contains a viroid-like, 1.7-kb circular RNA genome, which replicates via a double-rolling-circle model. However, the exact mechanism involved in HDV genome RNA replication and subgenomic mRNA transcription is still unclear. Our previous studies have shown that the replications of genomic and antigenomic HDV RNA strands have different sensitivities to α-amanitin and are associated with different nuclear bodies, suggesting that these two strands are synthesized in different transcription machineries in the cells. In this study, we developed a unique quantitative reverse transcription-PCR (qRT-PCR) procedure for detection of various HDV RNA species from an RNA transfection system. Using this qRT-PCR procedure and a series of HDV mutants, we demonstrated that Arg-13 methylation, Lys-72 acetylation, and Ser-177 phosphorylation of small hepatitis delta antigen (S-HDAg) are important for HDV mRNA transcription. In addition, these three S-HDAg modifications are dispensable for antigenomic RNA synthesis but are required for genomic RNA synthesis. Furthermore, the three RNA species had different sensitivities to acetylation and deacetylation inhibitors, showing that the metabolic requirements for the synthesis of HDV antigenomic RNA are different from those for the synthesis of genomic RNA and mRNA. In sum, our data support the hypothesis that the cellular machinery involved in the synthesis of HDV antigenomic RNA is different from that of genomic RNA synthesis and mRNA transcription, even though the antigenomic RNA and the mRNA are made from the same RNA template. We propose that acetylation and deacetylation of HDAg may provide a molecular switch for the synthesis of the different HDV RNA species.